Management of noma: practice competence and knowledge among healthcare workers in a rural district of Zambia. Issue 1 (1st January 2017) - Ahlgren, Mathilda; Funk, Tjede; Marimo, Clemence; Ndiaye, Charlotte; Alfvén, Tobias
ABSTRACT: Background : Noma is an infectious but opportunistic disease that often results in severe facial disfigurements and mortality if untreated. As noma progresses quickly, early detection and treatment are important to prevent its development. Objectives : The objective of this study was to investigate primary healthcare workers' knowledge and management of noma in a rural part of Zambia. Methods : A cross-sectional self-completed survey was conducted among 35 healthcare workers from two district hospitals and 15 rural health centres in Serenje District, Zambia. Participants' practice competences and knowledge were grouped into 'optimal', 'medium', 'suboptimal' and 'very low'. Results : Most of the healthcare workers stated that they perform mouth examination of a child below five years of age who is suffering from measles, malnutrition or HIV. A majority diagnosed gingivitis correctly and 40% had a medium level of practice competence of the same noma stage. All participants had a suboptimal or very low level on overall practice competence regarding management of noma and two-thirds had a very low level of reported knowledge. Conclusion : General knowledge on noma and competences of diagnosing and treating noma patients was low among healthcare workers. Lack of knowledge could present a barrier for correctly managing noma at an early stage. Improving knowledge among healthcare workers is one way to prevent the development of the disease. In order to prevent noma from the start, actions need to be focussed on improving (oral) hygiene and health education as well. Telemedicine could also be considered as it can help healthcare workers in handling noma patients through enabling communication and exchange of information with specialist.